The numerical simulation of plate-type windborne debris flight - Kakimpa, Bruce (2012)
Wind borne debris is one of the principal causes of building envelope failure during severe storms. It is often of interest in windstorm risk modelling to estimate the potential flight trajectories and impact energy of a piece of debris. This thesis presents research work aimed at the development and validation of a numerical model for the simulation of plate-type windborne debris. While a number of quasi-steady analytical models are available at present, these models are unable to account for the fluid-plate interaction in highly unstable flows. The analytical models are also limited to simple launch flow conditions and require extensive a-priori knowledge of the debris aerodynamic characteristics. In addition, the use of Euler angle parametrisations of orientation in the analytical models results in mathematical singularities when considering 3D six degree-of-freedom motion.